CAUSATIVE AGENT OF BACTEREMIA AND INTESTINAL MICROBIOTA IN RECIPIENTS OF DONOR LIVER - N. I. Gabrielyan; E. M. Gorskaya; I. V. Drapkina; T. S. Spirina; O. M. Tsiroulnikova (Вестник трансплантологии и искусственных органов)
Aim. To study microbiota of the intestinal tract of recipients with cirrhosis of the liver lobes before transplantation and its association with postoperative bacteremia pathogens.Materials and methods. Microbiota of the intestinal tract was studied in 235 recipients (1–17 years) prior to transplantation of the liver fragment from a related donor (2005–2014). Microbiological study of intestinal contents, trachea, blood, vascular catheters was performed by plating a material on the standard culture medium. Identifi cation was carried out using microbial BD Crystal panels and BBL Crystal MIND databases. Susceptibility of isolated opportunistic bacteria to antibiotics was investigated by disk diffusion method.Results. Deep microecological disturbances in the intestinal tract in childrenwere revealed. All recipients showed the reduction of resident microbiota with reduced content of bifi dobacteria, lactobacilli and coliform bacteria. The growth rate of isolating opportunistic Gram-negative bacteria, especially Klebsiella and enterobacteria (up 100%) was detected. Non-fermenting Gram-negative bacteria, in particularly, Pseudomonas aeruginosa were isolated rarely. Among Gram-positive bacteria dominated coagulase-negative staphylococci (CoNS). In patients with unremarkable post-transplant period (Group 1) CoNS and enterococci were often isolated. In the blood of patients with complicated postoperative period (Group 2) Pseudomonas aeruginosa (44%) and Klebsiella pneumoniae (36%) were isolated. Similar microorganisms were seeded from vascular catheters of the same patients. It is worth noting that no essential differences in the content of Klebsiella and non-fermenting microorganisms in microbiota of the intestinal tract of the recipients of both groups were not determined.Conclusion. Studies showed deep microecological disorders of the intestinal microbiota. Klebsiella pneumonia was the main pathogen, whose high content was detected in all liver lobe recipients studied. Isolation of Klebsiella pneumonia in the blood was 23,7% in patients with complicated postoperative period, and 12,9% in those with unremarkable post-transplant period. No such dependence was revealed in relation to Pseudomonas aeroginosa.